Tire inner liner rubber composite material with high bio-based content and excellent air tightness and preparation method thereof
By using high biological base content in the tire air dense layer of rubber material, the high biological base content is composite for cutamate rubber rubber and halogen -butyl rubber, solving the problem of insufficient biological base content and gas tight in existing technologies, and achieved higher gas gas Dean and aging resistance, support the sustainable development of tires.
Patent Information
- Application Number
- CN202411221531.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-02
AI Technical Summary
The existing tire airtight rubber materials have challenges in improving biobase content and airtightness, resulting in poor gas-saving performance and service life of tires. At the same time, relying on non-renewable petrochemical resources, affecting sustainable development.
Adopt high biological base content, composite osteate rubber and halogen -l -lipplastic rubber composite materials, and improve the vulgarity and aging resistance by designing a suitable sulfur system, auxiliary system and processing technology.
The tire composite rubber composite material with high biological base content and excellent gas tires is achieved, reducing the dependence of petrochemical raw materials, and improving the service life and environmental performance of the tire.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure FDA0005023181010000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of tire airtight layer rubber composite materials, and relates to a rubber composite material and a preparation method and application thereof, and in particular to a tire airtight layer rubber composite material with high bio-based content and excellent airtightness, and a preparation method and application thereof. Background Art
[0002] With the popularity of new energy vehicles, higher requirements are placed on the load-bearing capacity and instantaneous torque of tires, which in turn places higher requirements on tire air tightness. Insufficient tire inflation can lead to increased rolling resistance, slow handling response, longer braking distance, uneven tire wear, and increased stress on internal tire components, which can cause tire blowouts and other problems.
[0003] The air tightness of a tire is mainly determined by the innermost rubber layer of the tire, which is also the airtight layer. Highly airtight composite materials provide an application solution for new energy vehicles to reduce the thickness of the airtight layer and reduce the rolling resistance of the tire. In addition, bio-based composite materials are also in line with the country's environmental protection concept.
[0004] In the prior art, the base rubber of the tire airtight layer is mostly a combination of natural rubber and halogenated butyl rubber. The main problem with this combination is that as the amount of natural rubber used increases, the air permeability coefficient of the airtight layer will increase, thereby reducing the tire's air retention performance and affecting the tire's service life and driving controllability.
[0005] On the other hand, the main raw materials of butyl rubber used in the tire industry, such as isobutylene and isoprene, are all derived from non-renewable petrochemical resources. As a major consumer of petrochemical resources, the rubber industry produces a large amount of wastewater and waste gas. The development of biomass energy and bio-based chemicals has gradually attracted attention from countries around the world, as they have large reserves and are carbon neutral. The development of bio-based synthetic elastomer composites based on bio-based chemicals is of great significance for sustainable development. Under the influence of relevant policies, making full use of low-carbon and renewable resources has been paid attention to by countries around the world. Among the raw materials used in tire production, most of them are heavily dependent on rubber materials synthesized from fossil resources, with high carbon emissions, which is very unfavorable to the sustainable development of the tire industry. Although compared with traditional petroleum-based materials, bio-based materials have large reserves, are carbon neutral, and have advantages such as reducing raw material costs, existing research has gradually tried to use bio-based materials in many aspects, but the product performance is still not ideal. With the accelerated implementation of the green transformation and upgrading of the rubber additive industry and the increasing environmental pressure, various environmentally friendly additives have been gradually applied to various rubber products. The use of new environmentally friendly, non-toxic natural materials, green additives and other safe and environmentally friendly materials to replace various traditional additives is of great significance to the sustainable development of the transmission belt industry and is also the main direction of technological development.
[0006] Therefore, how to obtain a suitable production process and rubber composite material to solve the above-mentioned problems existing in existing processes and rubber products, especially tire airtight layer rubber materials, and further improve the level of green environmental protection has become an important issue that many front-line production R&D personnel and industry manufacturers in the industry need to solve urgently. Summary of the invention
[0007] In view of this, the technical problem to be solved by the present invention is to provide a rubber composite material and its preparation method and application, in particular, a tire airtight layer rubber composite material with high bio-based content and excellent airtightness. The airtight layer rubber provided by the present invention includes environmentally friendly bio-based itaconate rubber, which is beneficial to energy saving and carbon reduction. At the same time, because itaconate rubber has certain side groups and is arranged more closely, it has certain gas barrier properties; its composite with butyl rubber has better airtightness and aging resistance than natural rubber. In addition, the airtight layer rubber has a simple processing technology, low equipment requirements, and excellent processing performance, and is suitable for wide use.
[0008] The present invention provides a rubber composite material, which comprises, by weight of raw materials:
[0009] 100 parts by weight of raw rubber;
[0010] The raw rubber includes itaconate rubber and halogenated butyl rubber;
[0011]
[0012] Preferably, in the raw rubber, the mass ratio of halogenated butyl rubber to itaconate rubber is (1-9):1;
[0013] The itaconate rubber is a binary, ternary or tetrapolymer containing itaconate and a bio-based diene or a petroleum-based conjugated diene;
[0014] The itaconate rubber is specifically a copolymer obtained by low-temperature emulsion polymerization of raw materials including dibutyl itaconate units and butadiene units;
[0015] The polymerization temperature of the low-temperature emulsion polymerization is 1-20°C.
[0016] Preferably, the itaconate is selected from one or more of dimethyl itaconate, diethyl itaconate, di-n-propyl itaconate, di-n-butyl itaconate, diisopropyl itaconate, diisobutyl itaconate, di-n-pentyl itaconate and diisopentyl itaconate;
[0017] The bio-based dienes are dienes produced by microbial fermentation or terpenes derived from plants;
[0018] The petroleum-based conjugated diene is isoprene and / or butadiene;
[0019] The rubber composite material is a rubber composite material used for a tire airtight layer.
[0020] Preferably, the itaconate rubber further comprises a third component and / or a fourth component;
[0021] The third component and the fourth component are independently selected from one or more of glycidyl methacrylate, styrene, vinyl chloroacetate, acrylamide, cyclopentadiene, ethylidene norbornene, methyl acrylate, ethyl acrylate, methoxyethyl acrylate, ethoxyethyl acrylate, hydroxyethyl methacrylate and 2-hydroxyethyl acrylate;
[0022] The reinforcing filler is one or more of carbon black, pyrolysis carbon black, calcium carbonate, calcium sulfate, dolomite powder, clay, clay, montmorillonite, clay, montmorillonite barium sulfate, talc, magnesium carbonate, magnesium silicate, graphene and cellulose bio-based filler;
[0023] The vulcanizing agent is sulfur.
[0024] Preferably, the activator is one or more of zinc oxide, stearic acid and magnesium oxide;
[0025] The plasticizer is one or more of naphthenic oil, aromatic oil, petroleum resin, epoxidized soybean oil and palm oil;
[0026] The homogenizer is an aromatic hydrocarbon resin mixture;
[0027] The tackifying resin is phenolic resin and / or petroleum resin;
[0028] The accelerator is one or more of thiazole accelerators, thiuram accelerators, dithiocarbamate accelerators, xanthate accelerators, guanidine accelerators, aldehyde amine accelerators, sulfonamide accelerators and thiourea accelerators.
[0029] The present invention provides a method for preparing a rubber composite material as described in any one of the above technical solutions, comprising the following steps:
[0030] 1) The raw rubber is plasticized in an internal mixer to obtain plasticized rubber;
[0031] 2) adding a reinforcing filler, a plasticizer, magnesium oxide, a homogenizer and a tackifying resin to the plasticized rubber obtained in the above step, mixing the mixture, and then removing the rubber to obtain a masterbatch;
[0032] 3) After cooling the first stage masterbatch obtained in the above step, the first stage masterbatch, the vulcanizing agent, the activator and the accelerator are further mixed, and the mixture is discharged to obtain the second stage final mixing;
[0033] 4) The second-stage final rubber mix obtained in the above step is thin-passed on an open mixing mill to obtain a mixed rubber, which is then vulcanized to obtain a rubber composite material.
[0034] Preferably, the mastication time is 0.5 to 1.5 min;
[0035] The temperature of the plasticizing is 40 to 80°C;
[0036] The speed of the internal mixer during plastication is 40 to 80 rpm;
[0037] The mixing temperature is 110-150°C;
[0038] The mixing time is 4 to 8 minutes.
[0039] Preferably, the temperature after cooling is less than or equal to 80°C;
[0040] The temperature of the continued banburying is 90-130°C;
[0041] The time of continuing the banburying is 1 to 3 minutes;
[0042] The number of thin passes is 3 to 12 times;
[0043] The roller distance of the thin pass is 0.5-4.0 mm.
[0044] Preferably, the thin-pass further comprises a parking step;
[0045] The parking time is 18 to 24 hours;
[0046] The vulcanization temperature is 130-180°C;
[0047] The vulcanization time is 5 to 60 minutes;
[0048] The vulcanization pressure is 20 to 40 tons.
[0049] The present invention provides the use of the rubber composite material described in any one of the above technical solutions or the rubber composite material prepared by the preparation method described in any one of the above technical solutions in tires.
[0050] The present invention provides a rubber composite material, which comprises, by weight of raw materials, 100 parts by weight of raw rubber, 40 to 100 parts by weight of reinforcing filler, 2 to 10 parts by weight of activator, 4 to 10 parts by weight of plasticizer, 2 to 15 parts by weight of homogenizer, 2 to 15 parts by weight of tackifying resin, 0.05 to 0.5 parts by weight of magnesium oxide, 1.0 to 6.0 parts by weight of accelerator and 0.5 to 3 parts by weight of vulcanizing agent; the raw rubber comprises itaconate rubber and halogenated butyl rubber. Compared with the prior art, the present invention particularly adopts itaconate bio-based rubber as a matrix material, designs a vulcanization system, an auxiliary agent system and a processing technology, and designs a tire airtight layer rubber composite material with high bio-based content and excellent air tightness. The airtight layer rubber provided by the present invention comprises environmentally friendly bio-based itaconate rubber, which is beneficial to energy conservation and carbon reduction. At the same time, since the itaconate rubber has certain side groups and is arranged relatively tightly, it has certain gas barrier properties. Its composite with butyl rubber has better air tightness and aging resistance than natural rubber.
[0051] The present invention replaces natural rubber or halogenated butyl rubber in the traditional airtight layer formula with bio-based itaconate rubber prepared from biomass resources in equal amounts, reducing dependence on petrochemical raw materials. At the same time, the obtained high-biobased airtight layer rubber composite material has better low permeability, aging resistance and fatigue resistance than the same amount of natural rubber, and other basic mechanical properties also meet the requirements, which can greatly improve the service life of the tire and comply with relevant policies.
[0052] In addition, the present invention also provides a corresponding preparation method, which has a simple processing technology, low requirements on equipment, and excellent processing performance, and is more suitable for promotion and application of large-scale industrial production. DETAILED DESCRIPTION
[0053] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.
[0054] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0055] The present invention provides a rubber composite material, which comprises, by weight of raw materials:
[0056] 100 parts by weight of raw rubber;
[0057] The raw rubber includes itaconate rubber and halogenated butyl rubber;
[0058] 40 to 100 parts by weight of reinforcing filler;
[0059] 2 to 10 parts by weight of activator;
[0060] 4 to 10 parts by weight of plasticizer;
[0061] 2 to 15 parts by weight of a homogenizing agent;
[0062] 2 to 15 parts by weight of tackifying resin;
[0063] 0.05-0.5 parts by weight of magnesium oxide;
[0064] 1.0 to 6.0 parts by weight of accelerator;
[0065] Vulcanizing agent 0.5 to 3 parts by weight.
[0066] In the present invention, the content of the reinforcing filler is 40 to 100 parts by weight, can be 50 to 90 parts by weight, can be 60 to 80 parts by weight.
[0067] In the present invention, the content of the activator is 2 to 10 parts by weight, can be 3 to 9 parts by weight, can be 4 to 8 parts by weight, can be 5 to 7 parts by weight.
[0068] In the present invention, the content of the plasticizer is 4 to 10 parts by weight, can be 5 to 9 parts by weight, can be 6 to 8 parts by weight.
[0069] In the present invention, the content of the homogenizer is 2 to 15 parts by weight, can be 5 to 12 parts by weight, can be 8 to 9 parts by weight.
[0070] In the present invention, the content of the tackifying resin is 2 to 15 parts by weight, can be 5 to 12 parts by weight, can be 8 to 9 parts by weight.
[0071] In the present invention, the content of magnesium oxide is 0.05 to 0.5 parts by weight, can be 0.1 to 0.4 parts by weight, can be 0.2 to 0.3 parts by weight.
[0072] In the present invention, the content of the accelerator is 1.0 to 6.0 parts by weight, can be 2.0 to 5.0 parts by weight, can be 3.0 to 4.0 parts by weight.
[0073] In the present invention, the content of the vulcanizing agent is 0.5 to 3 parts by weight, can be 1.0 to 2.5 parts by weight, can be 1.5 to 2.0 parts by weight.
[0074] In the present invention, in the raw rubber, the mass ratio of the halogenated butyl rubber to the itaconate rubber is preferably (1-9):1, more preferably (2-8):1, more preferably (3-7):1, and more preferably (4-6):1.
[0075] In the present invention, the itaconate rubber is preferably a binary, ternary or tetrapolymer containing itaconate and a bio-based diene or a petroleum-based conjugated diene.
[0076] In the present invention, the itaconate rubber is preferably a copolymer obtained by low-temperature emulsion polymerization of raw materials including dibutyl itaconate units and butadiene units. Specifically, the itaconate rubber may be one or more of ItBR6600, ItBR6610, ItBR4710 and ItBR7410, and preferably ItBR6600.
[0077] In the present invention, the itaconate rubber is preferably a copolymer obtained by low-temperature emulsion polymerization of raw materials including dibutyl itaconate units and butadiene units, such as itaconate rubber with the brand ItBR6600. For details, please refer to the preparation method of itaconate / butadiene copolymer type bioengineering rubber disclosed in the Chinese patent application publication number CN104945817A, which specifically introduces the prepared bio-based itaconate rubber.
[0078] In the present invention, the polymerization temperature of the low-temperature emulsion polymerization is preferably 1 to 20°C, more preferably 5 to 16°C, and more preferably 9 to 12°C.
[0079] In the present invention, the itaconate is preferably selected from one or more of dimethyl itaconate, diethyl itaconate, di-n-propyl itaconate, di-n-butyl itaconate, diisopropyl itaconate, diisobutyl itaconate, di-n-pentyl itaconate and diisopentyl itaconate, more preferably dimethyl itaconate, diethyl itaconate, di-n-propyl itaconate, di-n-butyl itaconate, diisopropyl itaconate, diisobutyl itaconate, di-n-pentyl itaconate or diisopentyl itaconate.
[0080] In the present invention, the bio-based diene is preferably a diene produced by microbial fermentation or a terpene derived from a plant.
[0081] In the present invention, the petroleum-based conjugated diene is preferably isoprene and / or butadiene, more preferably isoprene or butadiene.
[0082] In the present invention, the rubber composite material is preferably a rubber composite material for a tire inner liner.
[0083] In the present invention, the itaconate rubber preferably further comprises a third component and / or a fourth component, more preferably the third component or the fourth component.
[0084] In the present invention, the third component and the fourth component are each independently preferably selected from one or more of glycidyl methacrylate, styrene, vinyl chloroacetate, acrylamide, cyclopentadiene, ethylidene norbornene, methyl acrylate, ethyl acrylate, methoxyethyl acrylate, ethoxyethyl acrylate, hydroxyethyl methacrylate and 2-hydroxyethyl acrylate, more preferably glycidyl methacrylate, styrene, vinyl chloroacetate, acrylamide, cyclopentadiene, ethylidene norbornene, methyl acrylate, ethyl acrylate, methoxyethyl acrylate, ethoxyethyl acrylate, hydroxyethyl methacrylate or 2-hydroxyethyl acrylate.
[0085] In the present invention, the reinforcing filler is preferably one or more of carbon black, pyrolysis carbon black, calcium carbonate, calcium sulfate, dolomite powder, clay, clay, montmorillonite, clay, montmorillonite barium sulfate, talc, magnesium carbonate, magnesium silicate, graphene and cellulose bio-based filler, more preferably carbon black, pyrolysis carbon black, calcium carbonate, calcium sulfate, dolomite powder, clay, clay, montmorillonite, clay, montmorillonite barium sulfate, talc, magnesium carbonate, magnesium silicate, graphene or cellulose bio-based filler.
[0086] In the present invention, the vulcanizing agent is preferably sulfur;
[0087] In the present invention, the mass content of the bio-based raw materials (bio-based content, mass content) of the rubber composite material is preferably 45-60%, more preferably 48-57%, and more preferably 51-54%. Compared with the existing rubber composite material for airtight layer, the present invention has better air tightness at the same amount of natural rubber.
[0088] In the present invention, the activator is preferably one or more of zinc oxide, stearic acid and magnesium oxide, more preferably zinc oxide, stearic acid or magnesium oxide.
[0089] In the present invention, the plasticizer is preferably one or more of naphthenic oil, aromatic oil, petroleum resin, epoxidized soybean oil and palm oil, more preferably naphthenic oil, aromatic oil, petroleum resin, epoxidized soybean oil or palm oil.
[0090] In the present invention, the homogenizer is preferably an aromatic hydrocarbon resin mixture, and specifically, the grade of the homogenizer may be 40MSF.
[0091] In the present invention, the tackifying resin is preferably phenolic resin and / or petroleum resin, more preferably phenolic resin or petroleum resin. Specifically, the petroleum resin may be C5 petroleum resin and / or C9 petroleum resin.
[0092] In the present invention, the accelerator is preferably one or more of thiazole accelerators, thiuram accelerators, dithiocarbamate accelerators, xanthate accelerators, guanidine accelerators, aldehyde amine accelerators, sulfonamide accelerators and thiourea accelerators, more preferably thiazole accelerators, thiuram accelerators, dithiocarbamate accelerators, xanthate accelerators, guanidine accelerators, aldehyde amine accelerators, sulfonamide accelerators or thiourea accelerators.
[0093] The present invention provides a method for preparing a rubber composite material as described in any one of the above technical solutions, comprising the following steps:
[0094] 1) The raw rubber is plasticized in an internal mixer to obtain plasticized rubber;
[0095] 2) adding a reinforcing filler, a plasticizer, magnesium oxide, a homogenizer and a tackifying resin to the plasticized rubber obtained in the above step, mixing the mixture, and then removing the rubber to obtain a masterbatch;
[0096] 3) After cooling the first stage masterbatch obtained in the above step, the first stage masterbatch, the vulcanizing agent, the activator and the accelerator are further mixed, and the mixture is discharged to obtain the second stage final mixing;
[0097] 4) The second-stage final rubber mix obtained in the above step is thin-passed on an open mixing mill to obtain a mixed rubber, which is then vulcanized to obtain a rubber composite material.
[0098] The invention firstly plasticates the raw rubber in an internal mixer to obtain plasticated rubber.
[0099] In the present invention, the mastication time is preferably 0.5 to 1.5 min, more preferably 0.7 to 1.3 min, and more preferably 0.9 to 1.1 min.
[0100] In the present invention, the temperature of the mastication is preferably 40 to 80°C, more preferably 48 to 72°C, and even more preferably 56 to 64°C.
[0101] In the present invention, the rotation speed of the internal mixer during the plasticating is preferably 40 to 80 rpm, more preferably 48 to 72 rpm, and more preferably 56 to 64 rpm.
[0102] In the present invention, reinforcing filler, plasticizer, magnesium oxide, homogenizer and tackifying resin are added to the plasticized rubber obtained in the above steps for mixing, and then the rubber is discharged to obtain a masterbatch.
[0103] In the present invention, the kneading temperature is preferably 110 to 150°C, more preferably 115 to 145°C, more preferably 120 to 140°C, and more preferably 125 to 135°C.
[0104] In the present invention, the kneading time is preferably 4 to 8 min, more preferably 4.5 to 7.5 min, more preferably 5 to 7 min, and more preferably 5.5 to 6.5 min.
[0105] The present invention then cools the first stage masterbatch obtained in the above steps, and then continues to mix the first stage masterbatch, the vulcanizing agent, the activator and the accelerator, and discharges the masterbatch to obtain the second stage final mix.
[0106] In the present invention, the temperature after cooling is preferably less than or equal to 80°C.
[0107] In the present invention, the temperature of the continued banburying is preferably 90-130°C, more preferably 95-125°C, more preferably 100-120°C, more preferably 105-115°C.
[0108] In the present invention, the time for continuing the banburying is preferably 1 to 3 minutes, more preferably 1.4 to 2.6 minutes, and more preferably 1.8 to 2.2 minutes.
[0109] In the present invention, the second-stage final rubber mix obtained in the above steps is finally thin-passed on an open mixing mill to obtain a mixed rubber, which is then vulcanized to obtain a rubber composite material.
[0110] In the present invention, the number of thin passes is preferably 3 to 12 times, more preferably 5 to 10 times, more preferably 7 to 9 times, and specifically may be 6 times.
[0111] In the present invention, the roller distance of the thin pass is preferably 0.5 to 4.0 mm, more preferably 1.0 to 3.5 mm, more preferably 1.5 to 3.0 mm, more preferably 2.0 to 2.5 mm.
[0112] In the present invention, the thin-pass process preferably further includes a parking step.
[0113] In the present invention, the parking time is preferably 18 to 24 hours, more preferably 19 to 23 hours, and more preferably 20 to 22 hours.
[0114] In the present invention, the vulcanization temperature is preferably 130 to 180°C, more preferably 140 to 170°C, and even more preferably 150 to 160°C.
[0115] In the present invention, the vulcanization time is preferably 5 to 60 min, more preferably 15 to 50 min, and more preferably 25 to 40 min.
[0116] In the present invention, the vulcanization pressure is preferably 20 to 40 tons, more preferably 24 to 36 tons, and even more preferably 28 to 32 tons (t).
[0117] The present invention provides the use of the rubber composite material described in any one of the above technical solutions or the rubber composite material prepared by the preparation method described in any one of the above technical solutions in tires.
[0118] The present invention is to complete and refine the overall technical solution, better ensure the composition and ratio of the rubber composite material, and further improve the comprehensive performance of the rubber composite material. The above-mentioned tire airtight layer rubber composite material with high bio-based content and excellent airtightness and its preparation method and application may specifically include the following contents:
[0119] A high-air-tightness, high-biobased itaconate elastomer airtight layer adhesive and a preparation method thereof, which is prepared from raw materials including the following components:
[0120] 100 parts of raw rubber;
[0121] 40-100 parts of reinforcing filler;
[0122] 2 to 10 parts of activator;
[0123] 4-20 parts of plasticizer;
[0124] 2 to 15 parts of leveling agent;
[0125] 2 to 15 parts of tackifying resin;
[0126] 0.05-0.5 parts of magnesium oxide;
[0127] 1.0 to 6.0 parts of accelerator;
[0128] 0.5-3 parts of vulcanizing agent;
[0129] The raw rubber consists of halogenated butyl rubber and itaconate rubber in a mass ratio of 9:1 to 1:1.
[0130] The itaconate rubber is a binary, ternary or tetrapolymer containing itaconate and bio-based diene or petroleum-based conjugated diene, wherein the itaconate can be selected from one or two of dimethyl itaconate, diethyl itaconate, di-n-propyl itaconate, di-n-butyl itaconate, diisopropyl itaconate, diisobutyl itaconate, di-n-pentyl itaconate and diisopentyl itaconate, and the bio-based diene refers to one or more of terpenes such as isoprene, butadiene, myrcene, limonene, etc. produced by microbial fermentation or derived from plants. The petroleum-based conjugated diene is one of isoprene and butadiene. It may also contain other third or fourth components, including one or two of glycidyl methacrylate, styrene, vinyl chloroacetate, acrylamide, cyclopentadiene, ethylidene norbornene, methyl acrylate, ethyl acrylate, methoxyethyl acrylate, ethoxyethyl acrylate, hydroxyethyl methacrylate, and 2-hydroxyethyl acrylate.
[0131] The reinforcing filler can be one or more of carbon black or pyrolysis carbon black, calcium carbonate, calcium sulfate, dolomite powder, clay, clay, montmorillonite, clay, montmorillonite barium sulfate, talc, magnesium carbonate, magnesium silicate, graphene, and cellulose bio-based fillers.
[0132] The activator is composed of one or more of zinc oxide, stearic acid and magnesium oxide, wherein the zinc oxide is 1.5 to 5 parts, the stearic acid is 1 to 3 parts, and the magnesium oxide is 0 to 2.0 parts.
[0133] The plasticizer can be one or two of naphthenic oil, aromatic oil, and petroleum resin. Preferably, naphthenic oil can be selected in an amount of 5 to 8 parts, and bio-based plasticizers such as epoxidized soybean oil and palm oil can also be selected to increase the bio-based content in the formula.
[0134] The accelerator is selected from one or more of thiazole accelerators, thiuram accelerators, dithiocarbamate accelerators, xanthate accelerators, guanidine accelerators, aldehyde amine accelerators, sulfenamide accelerators and thiourea accelerators. Preferably, 1-3 parts of thiazole accelerators can be selected.
[0135] The vulcanizing agent may be sulfur.
[0136] The homogenizer is an aromatic hydrocarbon resin mixture.
[0137] The tackifying resin is one or more of phenolic resin and petroleum resin.
[0138] The present invention also provides a method for preparing the tire inner liner rubber composite material with a high bio-based content, which comprises the following steps:
[0139] (1) Plasticizing the raw rubber in an internal mixer according to a certain mass ratio;
[0140] (2) adding a reinforcing filler, a homogenizer, stearic acid, magnesium oxide, a tackifier and a plasticizer in expected weight portions to the plasticized rubber and mixing the mixture;
[0141] (3) When the temperature in the internal mixer reaches 110-150°C, the rubber is discharged to obtain a masterbatch;
[0142] (4) After the first stage of the masterbatch in step (3) is cooled, the masterbatch, sulfur, accelerator and activator are put into an internal mixer and continue to be mixed. When the temperature in the internal mixer reaches 90-130° C., the masterbatch is discharged to obtain the second stage of final mixing;
[0143] (5) The second-stage final rubber mix is thinned on an open mixing mill for 6 times, rolled off with a roller spacing of 2 mm, and allowed to stand to obtain an airtight layer rubber mix.
[0144] (6) The mixed rubber obtained in step (5) is tested for vulcanization properties using a rotorless vulcanizer, and a vulcanized rubber sample is obtained using a flat plate vulcanizer.
[0145] The mixing time of the masterbatch in the step is 4 to 8 minutes; the cooling temperature is less than 80°C;
[0146] The final mixing time is 1 to 3 minutes, the storage temperature is 20 to 30°C, and the time is 18 to 24 hours.
[0147] The vulcanization temperature is 130° C. to 180° C., the pressure is 20 tons to 40 tons, and the time is 5 minutes to 60 minutes.
[0148] The above content of the present invention provides a tire airtight layer rubber composite material with high bio-based content and excellent air tightness, and its preparation method and application. The present invention particularly adopts itaconate bio-based rubber as the matrix material, and designs the vulcanization system, auxiliary agent system and processing technology, etc., to design a tire airtight layer rubber composite material with high bio-based content and excellent air tightness. The airtight layer rubber provided by the present invention contains environmentally friendly bio-based itaconate rubber, which is beneficial to energy conservation and carbon reduction. At the same time, because itaconate rubber has certain side groups and is arranged more closely, it has certain gas barrier properties; its compound with butyl rubber has better air tightness and aging resistance than natural rubber.
[0149] The present invention replaces natural rubber or halogenated butyl rubber in the traditional airtight layer formula with bio-based itaconate rubber prepared from biomass resources in equal amounts, reducing dependence on petrochemical raw materials. At the same time, the obtained high-biobased airtight layer rubber composite material has better low permeability, aging resistance and fatigue resistance than the same amount of natural rubber, and other basic mechanical properties also meet the requirements, which can greatly improve the service life of the tire and comply with relevant policies.
[0150] In addition, the present invention also provides a corresponding preparation method, which has a simple processing technology, low requirements on equipment, and excellent processing performance, and is more suitable for promotion and application of large-scale industrial production.
[0151] In order to further illustrate the present invention, a rubber composite material provided by the present invention and its preparation method and application are described in detail below in combination with embodiments. However, it should be understood that these embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following embodiments.
[0152] In the following embodiments, itaconate rubber: Shandong Jingbo Zhongju New Materials Co., Ltd., commercially available brand ItBR6610, number average molecular weight of 220,000 to 320,000, weight average molecular weight of 650,000 to 900,000; natural rubber: commercially available, brand CV60, weight average molecular weight of 400,000 to 600,000; halogenated rubber: BIIR / CIIR, weight average molecular weight of 270,000 to 850,000; other raw and auxiliary materials are all commercially available products.
[0153] Example 1
[0154] A high-air-tightness, high-biobased itaconate elastomer airtight layer adhesive contains the following components, measured by mass: 80 parts of brominated butyl rubber, 20 parts of itaconate rubber, 60 parts of carbon black N660, 3 parts of zinc oxide, 1 part of stearic acid, 7 parts of leveling agent 40MSF, 4 parts of tackifying resin SP1068, 8 parts of aromatic oil, 1.2 parts of sulfur, 0.8 parts of accelerator DM, 1.0 parts of accelerator CBS, and 0.15 parts of magnesium oxide.
[0155] The steps of preparing a high air tightness, high bio-based itaconate elastomer airtight layer adhesive are as follows:
[0156] (1) masticating itaconate rubber and brominated butyl rubber in an internal mixer for 1.5 min at a speed of 70 rpm;
[0157] (2) adding carbon black N660, homogenizer, stearic acid, magnesium oxide, tackifier, and plasticizer in sequence for mixing, and when the temperature in the internal mixer reaches 130° C., the rubber is discharged to obtain a masterbatch;
[0158] (3) After the first stage masterbatch of step (2) is cooled and left to stand for more than 2 hours, the masterbatch, sulfur, accelerator and zinc oxide are put into an internal mixer and further mixed. When the temperature in the internal mixer reaches 110° C., the masterbatch is discharged to obtain the second stage final mix.
[0159] (4) The mixture was thinned on an open mixing mill for 6 times, rolled off with a roller distance of 2 mm, and left to stand at a temperature of 20 to 30° C. for 18 h to obtain a tire innerliner rubber compound.
[0160] (5) The mixed rubber obtained in step (4) is tested for vulcanization properties using a rotorless vulcanizer, and a vulcanized rubber sample is obtained using a flat plate vulcanizer.
[0161] The vulcanization temperature in the step (5) is 150-180°C.
[0162] Example 2
[0163] A high-air-tightness, high-biobased itaconate elastomer airtight layer rubber contains the following ingredients, measured by mass: 60 parts of brominated butyl rubber, 40 parts of itaconate rubber, 60 parts of carbon black N660, 3 parts of zinc oxide, 1 part of stearic acid, 7 parts of leveling agent 40MSF, 4 parts of tackifying resin SP1068, 8 parts of aromatic oil, 1.2 parts of sulfur, 0.8 parts of accelerator DM, 1.0 parts of accelerator CBS, and 0.15 parts of magnesium oxide.
[0164] The airtight layer adhesive composite material was prepared according to the same preparation method as in Example 1.
[0165] Example 3
[0166] A high-air-tightness, high-biobased itaconate elastomer airtight layer rubber contains the following ingredients, measured by mass: 50 parts of brominated butyl rubber, 50 parts of itaconate rubber, 60 parts of carbon black N660, 3 parts of zinc oxide, 1 part of stearic acid, 7 parts of leveling agent 40MSF, 4 parts of tackifying resin SP1068, 8 parts of aromatic oil, 1.2 parts of sulfur, 0.8 parts of accelerator DM, 1.0 parts of accelerator CBS, and 0.15 parts of magnesium oxide.
[0167] The airtight layer adhesive composite material was prepared according to the same preparation method as in Example 1.
[0168] Comparative Example 1
[0169] A high-air-tightness, high-biobased itaconate elastomer airtight layer adhesive contains the following ingredients, measured by mass: 80 parts of brominated butyl rubber, 20 parts of natural rubber, 60 parts of carbon black N660, 3 parts of zinc oxide, 1 part of stearic acid, 7 parts of leveling agent 40MSF, 4 parts of tackifying resin SP1068, 8 parts of aromatic oil, 1.2 parts of sulfur, 0.8 parts of accelerator DM, and 1.0 parts of accelerator CBS.
[0170] The airtight layer adhesive composite material was prepared according to the same preparation method as in Example 1.
[0171] Comparative Example 2
[0172] A high-air-tightness, high-biobased itaconate elastomer airtight layer adhesive contains the following ingredients, measured by mass: 60 parts of brominated butyl rubber, 40 parts of natural rubber, 60 parts of carbon black N660, 3 parts of zinc oxide, 1 part of stearic acid, 7 parts of leveling agent 40MSF, 4 parts of tackifying resin SP1068, 8 parts of aromatic oil, 1.2 parts of sulfur, 0.8 parts of accelerator DM, and 1.0 parts of accelerator CBS.
[0173] The airtight layer adhesive composite material is prepared according to the same preparation method as in Example 1. The performance comparison of the airtight layer adhesive composite materials prepared in the examples of the present invention is as follows, see Table 1, which shows the physical and mechanical performance test results of the airtight layer adhesive composite materials prepared in the examples of the present invention and the comparative examples.
[0174] Table 1
[0175]
[0176] It can be seen from Examples 1 to 3 and Comparative Examples 1 to 2 that the permeability coefficient of the airtight layer rubber composite material prepared in the embodiment of the present invention is reduced, the comprehensive performance is excellent, and the performance of 50 parts of bio-based itaconate rubber is still better than that of 40 parts of natural rubber, indicating that it is feasible to increase the bio-based content of the tire by using bio-based itaconate rubber; at the same time, the airtight layer composite material made of bio-based itaconate rubber has improved aging performance and fatigue performance, which helps to extend the service life of the tire, thereby extending the service life of the material and achieving the purpose of reducing carbon emissions. The present invention uses bio-based itaconate rubber prepared from renewable biomass resources to partially replace natural rubber or halogenated butyl rubber in the traditional formula, meets the requirements of green and low carbon, and is the current trend of sustainable green development.
[0177] The above is a detailed introduction to a tire airtight layer rubber composite material with high bio-based content and excellent air tightness provided by the present invention, and its preparation method and application. In this article, specific examples are used to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method and its core ideas of the present invention, including the best mode, and also enables any technician in the field to practice the present invention, including the manufacture and use of any device or system, and the implementation of any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A rubber composite material, characterized in that: Calculated by weight of raw materials, including: 100 parts by weight of raw rubber; The raw rubber includes itaconate rubber and halogenated butyl rubber; 2. The rubber composite material according to claim 1, characterized in that: In the raw rubber, the mass ratio of halogenated butyl rubber to itaconate rubber is (1-9):1; The itaconate rubber is a binary, ternary or tetrapolymer containing itaconate and a bio-based diene or a petroleum-based conjugated diene; The itaconate rubber is specifically a copolymer obtained by low-temperature emulsion polymerization of raw materials including dibutyl itaconate units and butadiene units; The polymerization temperature of the low-temperature emulsion polymerization is 1-20°C.
3. The rubber composite material according to claim 2, characterized in that: The itaconate ester is selected from one or more of dimethyl itaconate, diethyl itaconate, di-n-propyl itaconate, di-n-butyl itaconate, diisopropyl itaconate, diisobutyl itaconate, di-n-pentyl itaconate and diisopentyl itaconate; The bio-based dienes are dienes produced by microbial fermentation or terpenes derived from plants; The petroleum-based conjugated diene is isoprene and / or butadiene; The rubber composite material is a rubber composite material used for a tire airtight layer.
4. The rubber composite material according to claim 2, characterized in that: The itaconate rubber further comprises a third component and / or a fourth component; The third component and the fourth component are independently selected from one or more of glycidyl methacrylate, styrene, vinyl chloroacetate, acrylamide, cyclopentadiene, ethylidene norbornene, methyl acrylate, ethyl acrylate, methoxyethyl acrylate, ethoxyethyl acrylate, hydroxyethyl methacrylate and 2-hydroxyethyl acrylate; The reinforcing filler is one or more of carbon black, pyrolysis carbon black, calcium carbonate, calcium sulfate, dolomite powder, clay, clay, montmorillonite, clay, montmorillonite barium sulfate, talc, magnesium carbonate, magnesium silicate, graphene and cellulose bio-based filler; The vulcanizing agent is sulfur.
5. The rubber composite material according to claim 1, characterized in that: The activator is one or more of zinc oxide, stearic acid and magnesium oxide; The plasticizer is one or more of naphthenic oil, aromatic oil, petroleum resin, epoxidized soybean oil and palm oil; The homogenizer is an aromatic hydrocarbon resin mixture; The tackifying resin is phenolic resin and / or petroleum resin; The accelerator is one or more of thiazole accelerators, thiuram accelerators, dithiocarbamate accelerators, xanthate accelerators, guanidine accelerators, aldehyde amine accelerators, sulfonamide accelerators and thiourea accelerators.
6. A method for preparing the rubber composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) The raw rubber is plasticized in an internal mixer to obtain plasticized rubber; 2) adding a reinforcing filler, a plasticizer, magnesium oxide, a homogenizer and a tackifying resin to the plasticized rubber obtained in the above step, mixing the mixture, and then removing the rubber to obtain a masterbatch; 3) After cooling the first stage masterbatch obtained in the above step, the first stage masterbatch, the vulcanizing agent, the activator and the accelerator are further mixed, and the mixture is discharged to obtain the second stage final mixing; 4) The second-stage final rubber mix obtained in the above step is thin-passed on an open mixing mill to obtain a mixed rubber, which is then vulcanized to obtain a rubber composite material.
7. The preparation method according to claim 6, characterized in that: The mastication time is 0.5 to 1.5 minutes; The temperature of the plasticizing is 40 to 80°C; The speed of the internal mixer during plastication is 40 to 80 rpm; The mixing temperature is 110-150° C. The mixing time is 4 to 8 minutes.
8. The preparation method according to claim 6, characterized in that: The temperature after cooling is less than or equal to 80°C; The temperature of the continued banburying is 90-130°C; The time of continuing the banburying is 1 to 3 minutes; The number of thin passes is 3 to 12 times; The roller distance of the thin pass is 0.5-4.0 mm.
9. The preparation method according to claim 6, characterized in that: The thin pass also includes a parking step; The parking time is 18 to 24 hours; The vulcanization temperature is 130-180°C; The vulcanization time is 5 to 60 minutes; The vulcanization pressure is 20 to 40 tons.
10. Use of the rubber composite material according to any one of claims 1 to 5 or the rubber composite material prepared by the preparation method according to any one of claims 6 to 9 in tires.
Citation Information
Patent Citations
Itaconate / butadiene copolymer type bioengineering rubber and preparation method thereof
CN104945817A
Method for preparing itaconic ester / isoprene copolymer type bio-based engineering elastomer through low temperature emulsion polymerization
CN102558437A
Itaconate / isoprene copolymer type bio-based engineering elastomer and preparation method thereof
CN102558578A
Itaconate bio-based oil-resistant elastomer composite material and preparation method thereof
CN105968259A
Sole rubber material with high bio-based content as well as preparation method and application thereof
CN115975328A